Analysis of Sign Language in Learning Students with Special needs at SLB-B Beringin Bhakti Cirebon District - Solekha, Khofifatus; Baraja, Nabilah; Alfisah, Najwa Min; Siswoyo, Mukarto (Jurnal Greenation Sosial dan Politik, 2025)
This research aims to describe the effectiveness of using sign language in the learning process, especially at SLB-B Beringin Bhakti. The method used is qualitative with an observation and interview approach. This research describes adjustments in sign language to the learning process at the Beringin Bhakti SLB-B school. Communication is an important aspect in conveying ideas, information and feelings to speakers and listeners, while social development is a process for each individual in acquiring skills, values ??and behavior to interact with other people and the surrounding environment. This research found that the effectiveness of sign language in learning for deaf and speech impaired students depends on the communication and social environment in their school. This research also emphasizes that there is empathy and awareness from students, teaching and education staff and the surrounding environment to understand and accept shortcomings in sign language communication.